2012
DOI: 10.1016/j.vaccine.2012.05.072
|View full text |Cite
|
Sign up to set email alerts
|

A varicella outbreak in a school with high one-dose vaccination coverage, Beijing, China

Abstract: Background-Varicella vaccine is available in the private sector in China, with a single dose currently recommended for children aged ≥12 months. We investigated a varicella outbreak in a school in Beijing with high varicella vaccination coverage to describe the outbreak, examine risk factors for vaccine failure, and calculate vaccine effectiveness.Methods-A varicella case was defined as an acute generalized maculopapular rash without other apparent cause in a student without prior varicella attending the eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 17 publications
0
38
0
1
Order By: Relevance
“…47 Vaccination of healthcare workers should be considered as a priority. The increasing proportion of breakthrough cases in the outbreaks reported, and reported outbreaks in schools with high single-dose coverage, 8 indicate that a 2-dose vaccine regimen may need consideration for outbreak control or for routine childhood vaccination in Beijing.…”
Section: Discussionmentioning
confidence: 99%
“…47 Vaccination of healthcare workers should be considered as a priority. The increasing proportion of breakthrough cases in the outbreaks reported, and reported outbreaks in schools with high single-dose coverage, 8 indicate that a 2-dose vaccine regimen may need consideration for outbreak control or for routine childhood vaccination in Beijing.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the age of participants in the studies and vaccine recommendations in each country, the median time since vaccination is likely lower than 10 years. Within this time frame, some studies described a higher risk for vaccine failure with time since vaccination (using a cutoff of 3, 4, or 5 years), 22,26,28,[34][35][36] but other studies did not find this association 27,[37][38][39][40][41] ; in all these studies, conducted during outbreak investigations, the sample sizes were usually insufficient to assess the independent effect of time since vaccination as a risk factor. Four studies reported decline in VE with time since vaccination; however, the differences did not reach statistical significance.…”
Section: Figurementioning
confidence: 99%
“…2,3 This vaccine showed good short-term efficacy in clinical trials, 4 and in the first observational studies. [5][6][7] Over time, however, continued outbreaks in highly vaccinated populations and an increasing number vaccine failures 3,[8][9][10][11] led to the recommendation of a second dose. 12,13 Higher antibody titers are achieved with a second dose of varicella vaccine, 14 which suggests greater and longer lasting protection.…”
Section: Introductionmentioning
confidence: 99%